Screening and characterizing of xylanolytic and xylose-fermenting yeasts isolated from the wood-feeding termite, Reticulitermes chinensis - Ali, Sameh Samir (PLoS One, 2017)
The effective fermentation of xylose remains an intractable challenge in bioethanol industry. The relevant xylanase enzyme is also in a high demand from industry for several biotechnological applications that inevitably in recent times led to many efforts for screening some novel microorganisms for better xylanase production and fermentation performance. Recently, it seems that wood-feeding termites can truly be considered as highly efficient natural bioreactors. The highly specialized gut systems of such insects are not yet fully realized, particularly, in xylose fermentation and xylanase production to advance industrial bioethanol technology as well as industrial applications of xylanases. A total of 92 strains from 18 yeast species were successfully isolated and identified from the gut of wood-feeding termite, Reticulitermes chinensis. Of these yeasts and strains, seven were identified for new species: Candida gotoi, Candida pseudorhagii, Hamamotoa lignophila, Meyerozyma guilliermondii, Sugiyamaella sp.1, Sugiyamaella sp. 2, and Sugiyamaella sp.3. Based on the phylogenetic and phenotypic characterization, the type strain of C. pseudorhagii sp. nov., which was originally designated strain SSA-1542(T), was the most frequently occurred yeast from termite gut samples, showed the highly xylanolytic activity as well as D-xylose fermentation. The highest xylanase activity was recorded as 1.73 and 0.98 U/mL with xylan or D-xylose substrate, respectively, from SSA-1542(T). Among xylanase-producing yeasts, four novel species were identified as D-xylose-fermenting yeasts, where the yeast, C. pseudorhagii SSA-1542(T), showed the highest ethanol yield (0.31 g/g), ethanol productivity (0.31 g/L·h), and its fermentation efficiency (60.7%) in 48 h. Clearly, the symbiotic yeasts isolated from termite guts have demonstrated a competitive capability to produce xylanase and ferment xylose, suggesting that the wood-feeding termite gut is a promising reservoir for novel xylanases-producing and xylose-fermenting yeasts that are potentially valued for biorefinery industry.